2015
DOI: 10.1161/hypertensionaha.114.04463
|View full text |Cite
|
Sign up to set email alerts
|

Gαi 2 -Protein–Mediated Signal Transduction

Abstract: Excess dietary salt-intake is an established cause of hypertension. At present our understanding of the neuro-pathophysiology of salt-sensitive hypertension is limited by a lack of identification of the central nervous system mechanisms that modulate sympathetic outflow and blood pressure in response to dietary salt-intake. We hypothesized that impairment of brain Gαi2 protein-gated signal transduction pathways would result in increased sympathetically mediated renal sodium retention, thus promoting the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…A radiotelemetry probe (PA-C40, DSI, New Brighton, MN, USA) was implanted into the abdominal aorta via the left femoral artery and all animals recovered for 5-7 days prior to collection of baseline blood pressure data (Brouwers, Smolders, Wainford, & Dupont, 2015;Foss et al, 2015;Wainford, Carmichael, Pascale, & Kuwabara, 2015). ketamine, 3 mg kg −1 I.P.…”
Section: Radiotelemetry Probe Implantationmentioning
confidence: 99%
“…A radiotelemetry probe (PA-C40, DSI, New Brighton, MN, USA) was implanted into the abdominal aorta via the left femoral artery and all animals recovered for 5-7 days prior to collection of baseline blood pressure data (Brouwers, Smolders, Wainford, & Dupont, 2015;Foss et al, 2015;Wainford, Carmichael, Pascale, & Kuwabara, 2015). ketamine, 3 mg kg −1 I.P.…”
Section: Radiotelemetry Probe Implantationmentioning
confidence: 99%
“…A recent focus has been on the identification of potential mechanisms maintaining salt-resistance [ 39 41 ]. In the salt-resistant SD rat, in response to changes in dietary sodium intake, there is an endogenous PVN-specific increase (sodium excess) or decrease (sodium restriction) in guanine nucleotide binding protein alpha inhibiting activity binding polypeptide 2 (Gαi 2 ) protein expression [ 39 ].…”
Section: Advances In Hypothalamic Signaling In Salt-sensitive Hypertementioning
confidence: 99%
“…Acute and chronic downregulation of brain Gαi 2 proteins in high salt-challenged SD rats, which prevents endogenous PVN Gαi 2 protein upregulation, evokes sodium retention, global sympathoexcitation, and elevated blood pressure [ 39 , 40 ] suggesting a critical role of these proteins in maintaining salt-resistance. An endogenous sodium-evoked increase in PVN Gαi 2 protein expression has been documented in multiple salt-resistant phenotypes, as has a failure of this response in the DSS rat [ 41 ]. Further, brain Gαi 2 proteins are required to maintain salt-resistance, via a renal nerve-dependent pathway, in the salt-resistant SD and DSR rat [ 40 , 41 ].…”
Section: Advances In Hypothalamic Signaling In Salt-sensitive Hypertementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that high-salt insult promoted hypertension in association with activating angiotensin-aldosterone system [ 1 ], damaging renal natriuresis function [ 2 ], enhancing sympathetic activity [ 3 ], increasing the extracellular capacity, and eventually leading to sodium and water retention [ 4 ]. In addition, high salt could destroy the transfer passage of paraventricular nucleus G α i-protein gating signals [ 5 ]. However, the mechanisms for high-salt-induced hypertension remain unclear.…”
Section: Introductionmentioning
confidence: 99%